Radiofrequency catheter ablation of non-paroxysmal atrial fibrillation - A. Doronin; Y. Suslina; A. Riznyk; V. Khanenova; Y. Marushko; M. Meshkova (Ukrainian Journal of Cardiovascular Surgery, 2018)
In this article we analyzed our own experience of non-paroxysmal atrial fibrillation (AF) catheter ablations by conventional 4 mm tip non-irrigated catheters. The results of 120 primary sequential procedures are studied. Persistent form of AF was observed in 93 (77.5%) patients, long-standing persistent – in 27 (22.5%). The average time of X-ray exposure was 32.1±8.1 minutes, the number of applications was 109.4±19.4, the duration of the procedure was 2.7±0.6 hours. In 1 (0.8%) patient after the intervention there was an atrial tachycardia, in 1 (0.8%) – left atrial flutter. The recurrence of AF occurred in 34 (28.3%) patients. The sinus rhythm was preserved during the first year after ablation without the use of antiarrhythmic drugs in 80 (66.7%) patients. With the antiarrhythmic drugs administration we were able to maintain a sinus rhythm or make arrhythmia attacks rare in 23 (19.2%) patients. Thus, a positive effect of ablation was obtained in 103 (85.8%) patients. So, we can conclude that this ablation technique is quite effective in non-paroxysmal forms of AF.